Invertebrates, ecosystem services and climate change. (6th December 2012) - Prather, Chelse M.; Pelini, Shannon L.; Laws, Angela; Rivest, Emily; Woltz, Megan; Bloch, Christopher P.; Del Toro, Israel; Ho, Chuan‐Kai; Kominoski, John; Newbold, T. A. Scott; Parsons, Sheena; Joern, A.
ABSTRACT: The sustainability of ecosystem services depends on a firm understanding of both how organisms provide these services to humans and how these organisms will be altered with a changing climate. Unquestionably a dominant feature of most ecosystems, invertebrates affect many ecosystem services and are also highly responsive to climate change. However, there is still a basic lack of understanding of the direct and indirect paths by which invertebrates influence ecosystem services, as well as how climate change will affect those ecosystem services by altering invertebrate populations. This indicates a lack of communication and collaboration among scientists researching ecosystem services and climate change effects on invertebrates, and land managers and researchers from other disciplines, which becomes obvious when systematically reviewing the literature relevant to invertebrates, ecosystem services, and climate change. To address this issue, we review how invertebrates respond to climate change. We then review how invertebrates both positively and negatively influence ecosystem services. Lastly, we provide some critical future directions for research needs, and suggest ways in which managers, scientists and other researchers may collaborate to tackle the complex issue of sustaining invertebrate‐mediated services under a changing climate.